The Dosimetric Parameters Investigation of the Pulsed X-ray and Gamma Radiation Sources; Journal of Physics: Conference Series; Vol. 671 : Innovations in Non-Destructive Testing (SibTest 2015) - Stuchebrov S. G. Sergey Gennadevich (2016, 2016)
Title screen